Gott und Mensch Differenziologische Analysen zur Grammatik des Systems christlicher Existenz - Berg, Stefan (Mohr Siebeck, 2022)
Christian life takes its characteristic form by dealing with different things in different ways. This poses a key theological question: To whom should we attribute these distinctions? Stefan Berg traces how the grammar of the system of Christian existence unfolds as a series of re-entry movements.
PublicationDate: 20211207
Keywords: Hermeneutik -- Dogmatik -- Systemtheorie -- Systematische Theologie -- Religionsphilosophie